Estudo Químico de Plantas do Nordeste com atividade antioxidante: Senna martiana Benth (I. e B) - Macedo, Edângelo Moura Siqueira (2006)
This work presents the study of the chemical composition of Senna martiana (Benth) Irw. and Barn. belonging to the family of Leguminosas (subfamily Papilonoideae, synonym Fabaceae). this study was orientated for the volatile chemical representatives of the leaves knowledge and of the fixed representatives of the flowers and of the stem. Another object of interest was the evaluation of the antioxidant activity of the extracts hidroalcoólicos of the organs of the plant above mentioned. The bibliographical rising revealed the absence of studies phytochemistry, biological or pharmacológics accomplished with this species, reason for which the plant was selected for study. The study phytochemistry of the plant was accomplished using techniques as cromatographic for adsorption in open column (CC); cromatographic in thin layer (CCD), and in the determination of the structures technical such espectroscopic as: absorption in the area of the red band (IV); Nuclear Magnetic Resonance of Hydrogen (RMN 1H); Nuclear Magnetic Resonance of Carbon 13 (RMN 13C) united and bidimensionais. The volatile representatives extraction was accomplished by hidrodestilacion being used microwave oven as heating source and in the evaluation of the antioxidant activity it was used as analysis techniques, the capacity kidnapper of free radicals (method DPPH) and the measure of the antioxidant potential (method DHBA). The study of the fixed oil of the seeds of Senna martiana, resulted in the identification of fourteen graxos acids, being majority, the hexadecanoic acid (37%) and the 9,12-octadecanoic acid (34,1%). The study cromatographic of the extract ethanolic of the stem of Senna martiana made possible the isolation and identification of the triacontanoic acid (melíssico ac.), -sitosterol, of three anthraquinones 1,8-dihidroxylad, crysophanol, phyiscion and aloe-emodin, whose chemical identities were confirmed by the analysis of your spectra and comparison with the data of the literature. Among the isolated representatives it was obtained a heterosídeo of a bianthrone of the unpublished crysophanol in the literature.